Analisis Dampak Fenomena El Nino (1997-1998) Terhadap Ketersediaan Air Tanah Pulau Ambon - Rion Suaib Salman (Agrologia, 2015)
The availability of soil in water is needed to run an everyday life, especially for living beings. The availability of groundwater is highly dependent on the good hydrological patterns, whereby if rain occurs with sufficient criteria then groundwater will be available as much as we need, but if the hydrological cycle becomes disrupted as a result of meteorological phenomena such as el nino then it will decrease water content in the soil. El nino phenomenon that occurred in 1997-1998 had a profound influence on the availability of groundwater, especially on the island of Ambon. Based on the analysis of water balance on the island of Ambon in 1997-1998, water deficit (drought) was so significant in the mid to late 1997 and in 1998. This certainly greatly affected the agricultural sector which is very dependent on the availability of water ground. The dynamics of the atmosphere has changed significantly, Both the government and the other correspond institution must anticipate the impact of water shortages on agriculture.